2021
DOI: 10.1038/s41439-021-00151-z
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular diseases in two patients with entire NSD1 deletion

Abstract: We describe two patients with NSD1 deletion, who presented with early-onset, or recurrent cerebrovascular diseases (CVDs). A 39-year-old female showed developmental delay and abnormal gait in infancy, and developed slowly-progressive intellectual disability and movement disorders. Brain imaging suggested recurrent parenchymal hemorrhages. A 6-year-old male had tremor as a neonate and brain imaging revealed subdural hematoma and brain contusion. This report suggests possible involvement of CVDs associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…9 More recently, Itai et al reported a male with subdural hematoma and parenchymal hemorrhage in the posterior lobes in the neonatal period, as well as a 39-year-old woman with evidence of recurrent parenchymal hemorrhage. 10 Park et al additionally reported an infant with Sotos syndrome requiring a subduroperitoneal shunt at 10 months due to a severe subdural hygroma. 11 In addition to the above examples in the literature, the two cases presented herein suggest that some individuals with Sotos syndrome may be predisposed to SDH beginning in early infancy, possibly related to enlarged subdural spaces.…”
Section: Discussionmentioning
confidence: 99%
“…9 More recently, Itai et al reported a male with subdural hematoma and parenchymal hemorrhage in the posterior lobes in the neonatal period, as well as a 39-year-old woman with evidence of recurrent parenchymal hemorrhage. 10 Park et al additionally reported an infant with Sotos syndrome requiring a subduroperitoneal shunt at 10 months due to a severe subdural hygroma. 11 In addition to the above examples in the literature, the two cases presented herein suggest that some individuals with Sotos syndrome may be predisposed to SDH beginning in early infancy, possibly related to enlarged subdural spaces.…”
Section: Discussionmentioning
confidence: 99%
“…Cells derived from a patient with Soto’s syndrome hosting an NSD1-inactivating mutation was shown to have a global redistribution of the DNA methyltransferase DNMT3A, along with promoter DNA hypomethylation, dysregulated synapse formation, and dysregulated neurodevelopmental gene expression [ 129 131 ]. Moreover, individuals hosting NSD1 whole-gene deletions exhibited early-onset cerebrovascular diseases [ 132 ]. This phenotype was recapitulated by deletion of an NSD1 -like gene in fly, with developmental symptoms accompanied by global H3K36me2 reduction, defective motor and memory functions, and body size overgrowth [ 133 ].…”
Section: Histone H3k36 Di-methyl Transferasesmentioning
confidence: 99%